HUBUNGAN PENERAPAN MUSIK KERJA ISLAMI DENGAN KEJADIAN STRES KERJA DI SAKINAH SUPERMARKET - Jiana Rofik Baitur Rozaq (Universitas Airlangga, 2019)
Job stress is a physical and emotional disturbance as a result of a mismatch between capability, resources or the needs of workers coming from the worker's environment. Job stress is one of the most important issues discussed in the world of health, as some studies found its impacts on workers and productivity. To reduce the incidence of this work stress one of the Health Safety Environment (HSE) program was created. One of the Health Safety Environment (HSE) program which applied by Sakinah Supermarket is Islamic job music. The purpose of this study is to determine the relationship between Islamic music work with the incidence of job stress at Sakinah Supermarket. Quantitative research approach with cross sectional research design. The population in this research consist 68 workers, where research sample counted 40 workers. The variables studied were acceptance of Islamic music work and stressful work events. The data collection instrument used a questionnaire modification of the NIOSH Job Generic Stress Questionnaire. To test the relationship between variables Spearman correlation test used. The result of the research shows that workers' acceptance on Islamic music work in the high category (52.5%) is very high (45%) and the incidence of work stress does not exist where majority of respondents are in light work stress category (72.5%). Based on the Spearman correlation test the relationship between the two significant variables.Keywords: HSE program, islamic job music, job stress